Maternal knowledge on infant feeding in São Luís, Maranhão, Brazil - Paula Pizzatto; Caroline C Dalabona; Mariana Lima Correa; Nelson A Neumann; Juraci Almeida Cesar
Abtract Objectives: to describe the knowledge of infant feeding on breastfeeding and the introduction of complementary feeding among mothers of children under one-year-old in São Luís, MA. Methods: a cross-sectional descriptive study using a single questionnaire, standardized by trained interviewers, who visited all the residents in 20 communities chosen by convenience. This questionnaire searched for socioeconomic, demographic information, care received during pregnancy, and the knowledge about infant feeding. The analysis was performed through the creation of knowledge scores, frequency listing, central tendency and dispersion measurements. Results: among the 709 interviewees, 53.5% presented satisfactory knowledge. The score on the percentage mean of knowledge on infant feeding was 66.7%. The specific score on the introduction of complementary feeding was 60.7% and breastfeeding was71.4%. The benefits of breastfeeding for the babies were better known than the advantages it confers on mothers. The worst result was related to porridge preparation,(13.5%). Conclusion: the proportion of mothers who did not know about the basic teachings of infant feeding is high. This can lead to reduce exclusive breastfeeding time, increase rates of improper introduction of food and drink, and in favor early weaning.